Numerical investigation of nanofluid flow and heat transfer over a backward-facing step - Pournaderi, Pedram; Aram, Milad (Engineering and Applied Science Research, 2020)
In this research, the forced convection heat transfer of a nanofluid in a channel with a backward- facing step is studied by adopting the finite volume technique. The effect of nanoparticles is considered by employing the single-phase model. The influence of various parameters is considered on both pressure drop and Nusselt number. The local Nusselt number increases after the step as a result of the recirculation of flow. However, the average Nusselt number decreases as the step height increases. Increasing the step height also decreases the pressure drop. The pressure drop and Nusselt number both increases with nanoparticle’s concentration and Reynolds number. The pressure drop enhancement is very intense for the volume fraction of 0.04. Increasing nanoparticle diameter decreases both the pressure drop and Nusselt number. Six types of nanoparticles (TiO2, Fe3O4, CuO, Al2O3, ZnO, SiO2) were compared. The maximum average Nusselt number was related to Water-TiO2 nanofluid. It was also concluded that the effect of the nanofluid type on the pressure drop is not considerable. The performance index decreases with the Reynolds number slightly. Also, for concentrations of 3% and 4%, the performance index reduces considerably.